NILAI ANAK DAN JUMLAH ANAK YANG DIINGINKAN PASANGAN USIA SUBUR DI WILAYAH PERDESAAN DAN PERKOTAAN - Oktriyanto, Oktriyanto; Puspitawati, Herien; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2015)
This research aimed to analyze the value of children and preferred number of children among eligible couples in rural and urban areas. Specifically, the research examined the family characteristics, the value and preferred number of children, and the visit of family planning providers between rural and urban areas; and assessed the influence of the independent variables on preferred number of children. The design of the study was cross-sectional; and involeved 60 married women aged 15-49 years old from eligible couples who resided in Sirna Sari Village, Tanjung Sari, Bogor as a representative of rural areas and 60 of those who resided in Gudang Village, Bogor Tengah, Bogor as a representative of urban areas. The results of mean test confirmed that education level of both husband and women, the age of first marriage, the visit of family planning providers, the value of children, value of children in cost dimension, and preferred number of children were different among those who lived in rural and urban areas. Moreover, the results showed that region of residence, the age of first marriage among women, living children, family income per capita, and the visit of family planning providers affected significantly preferred number of children.